2019
DOI: 10.2174/1566524019666190308121552
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial tRNAHis G12192A Mutation May Modulate the Clinical Expression of Deafness-Associated tRNAThr G15927A Mutation in a Chinese Pedigree

Abstract: Background: Mutations in mitochondrial tRNA (mt-tRNA) genes have been found to be associated with both syndromic and non-syndromic hearing impairment. However, the pathophysiology underlying mt-tRNA mutations in clinical expression of hearing loss remains poorly understood. Objective: The aim of this study was to explore the potential association between mttRNA mutations and hearing loss. Methods and Results: We reported here the molecular features of a pedigree with maternally transmitted non-syndromic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…In this study, we found that 13 of the 25 tRNA genes shared by Rhizopogon species had site variations between the two Rhizopogon species. Mitochondrial tRNA mutation has been found to affect amino acid transport efficiency and protein synthesis in other eukaryotes [48,49]. The effects of tRNA variations on fungal growth and mitochondrial function are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that 13 of the 25 tRNA genes shared by Rhizopogon species had site variations between the two Rhizopogon species. Mitochondrial tRNA mutation has been found to affect amino acid transport efficiency and protein synthesis in other eukaryotes [48,49]. The effects of tRNA variations on fungal growth and mitochondrial function are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The tRNA and rRNA genes shared by the two Paxillus species also underwent base and length variations. Base variation in tRNA has been thought to affect the efficiency of amino acid transport and protein synthesis in animals (Ding et al 2019;Lin et al 2019). Further studies are needed to reveal the effect of tRNA variation on the growth and development of basidiomycete species.…”
Section: Gene Content Variation In Paxillus Speciesmentioning
confidence: 99%
“…To analysis the contributions of nuclear genes (GJB2, GJB3, GJB6 and TRMU) in the phenotypic manifestation of A1555G or C1494T-induced deafness, we performed a mutational analysis of these common nuclear genes from the matrilineal relatives (HZD501: II-6, III-4 and III-6; HZD502: III-3 and III-5; HZD503: II-10, III-9 and IV-4) by using the methods as described previously [22]. After PCR amplification and direct Sanger sequence, the data were compared with the wild-type versions of GJB2, GJB3, GJB6 and TRMU sequences (GenBank accession numbers: M86849, AF052692, NG 008323 and AF 448221, respectively) to detect the mutations or variants.…”
Section: Mutational Analysis Of Deafness-associated Nuclear Genesmentioning
confidence: 99%